Design of Phenylalanine-Containing Elastin-Derived Peptides Exhibiting Highly Potent Self-Assembling Capability - Maeda, Iori; Taniguchi, Suguru; Watanabe, Noriko; Inoue, Asako; Yamasaki, Yuko; Nose, Takeru (Protein and Peptide Letters, 2015)
In this study, we developed a series of Phe-containing elastin-derived peptide-analogs, (Phe-Pro-Gly-Val-Gly)n (n = 1–5) and analyzed their reversible coacervation properties. Compared to the native elastin-derived repeating peptide sequence ((Val-Pro-Gly-Val-Gly)10M), one of the Phecontaining 5-mer repeating peptide sequences ((Phe-Pro-Gly-Val-Gly)5) clearly exhibited stronger coacervation properties. The coacervation of (Phe-Pro-Gly-Val-Gly)5 is nearly the same as that of polypeptides (Val-Pro-Gly-Val-Gly)n (n > 40). Although large molecular weights (>10,000 Da) are generally required for the coacervation of elastin-derived peptides, (Phe-Pro-Gly-Val-Gly)5 exhibited reversible coacervation properties despite its low molecular weight (MW = 2,305 Da). High performance liquid chromatography (HPLC) and circular dichroism (CD) analysis revealed that (Phe-Pro-Gly-Val-Gly)5 has high hydrophobicity and an ordered structure with a type II β-turn, which contributes to the strong coacervation ability of the peptide. In addition, (Phe-Pro-Gly-Val-Gly)5 exhibited an effective particle size distribution (60–70 nm) at body temperature (37°C) and a dispersed small particle size similar to that of the monomer peptides at low temperatures. These properties, along with its small size and simple design, render the peptide suitable for use in biomaterials, including drug-delivery carriers.
Keywords: elastin